2021
DOI: 10.1186/s12885-021-09029-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of metal artifacts from knee tumor prostheses on CT images: value of the single energy metal artifact reduction (SEMAR) algorithm

Abstract: Background To evaluate the effect of the single energy metal artifact reduction (SEMAR) algorithm with a multidetector CT (MDCT) for knee tumor prostheses. Methods First, a phantom of knee tumor prosthesis underwent a MDCT scan. The raw data was reconstructed by iterative reconstruction (IR) alone and IR plus SEMAR. The mean value of the CT number and the image noise were measured around the prosthesis at the stem level and articular level. Second,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…iMAR has demonstrated its capability to reduce artifacts in various studies on most body regions, such as the spine, 3,4 the head, [4][5][6][7][8] for surgical clips, 9 the shoulder, 4 knees, 4,8 hips, 4,10 or the chest. 11,12 Other examples for clinical sinograminpainting-based MAR methods are single-energy MAR (SEMAR; Canon Medical Systems Corporation, Tustin, CA, USA) 13,14 or MAR for Orthopedic Implants (O-MAR; Philips Medical Systems, Amsterdam, Netherlands). 15,16 On the other hand, since its introduction in 2010, most recent publications on MAR in CT use NMAR 17 or its base-algorithm linear interpolation MAR (LIMAR) as their reference algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…iMAR has demonstrated its capability to reduce artifacts in various studies on most body regions, such as the spine, 3,4 the head, [4][5][6][7][8] for surgical clips, 9 the shoulder, 4 knees, 4,8 hips, 4,10 or the chest. 11,12 Other examples for clinical sinograminpainting-based MAR methods are single-energy MAR (SEMAR; Canon Medical Systems Corporation, Tustin, CA, USA) 13,14 or MAR for Orthopedic Implants (O-MAR; Philips Medical Systems, Amsterdam, Netherlands). 15,16 On the other hand, since its introduction in 2010, most recent publications on MAR in CT use NMAR 17 or its base-algorithm linear interpolation MAR (LIMAR) as their reference algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among various introduced approaches addressing MAR, sinogram inpainting has proven to be dominant in clinical routine. Examples for clinical implementations of sinogram inpainting are single-energy MAR (SEMAR, Canon Medical Systems Corporation 6,7 ), MAR for orthopedic implants (O-MAR, Philips Medical Systems 8,9 ), Smart MAR (GE Healthcare 10,11 ), and iterative MAR (iMAR, Siemens Healthcare GmbH [12][13][14] ). Sinogram inpainting addresses the correction of metal data by linearly interpolating in between metal projections in the sinogram domain.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been introduced to reduce the metal artifacts, including higher peak voltage, higher tube charge, MAR algorithms and dual-energy CT techniques [38,39]. However, higher peak voltage and tube charge may only reduce metal artifacts to a minor degree and may lead to a higher radiation dose for the patient [40]. Therefore, CT with metal artifact reduction (MAR) and dual-energy techniques are currently used to reduce the metal artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang at al. [40] showed that the SEMAR algorithm plus IR can significantly reduce metal artifacts and increase diagnostic confidence of prosthetic complications and tumor recurrence in patients with knee tumor prostheses than IR alone.…”
Section: Discussionmentioning
confidence: 99%